2022
DOI: 10.7759/cureus.28872
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Pericapsular Nerve Group (PENG) Block in Hip Surgeries Is Associated With a Reduction in Opioid Consumption, Less Motor Block, and Better Patient Satisfaction: A Meta-Analysis

Abstract: Pericapsular nerve group (PENG) block has been successfully utilized as an optional regional anesthesia approach to manage the pain for hip surgeries without affecting motor function. During recent years, the applications of PENG block are expanding. There is one previous review on PENG block for hip surgeries in the scientific literature and it is limited to case series and case reports only. We found few randomized controlled trials related to the role of PENG block in recent literature. So, a meta-analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 37 publications
1
15
1
1
Order By: Relevance
“…Statistically, PENG block seemed to be as effective as other types of nerve blocks for alleviating pain after hip surgery. We note that the pooled result of postoperative 24-h morphine consumption in published relevant meta-analysis is inconsistent with ours (27). Due to different perspectives and inclusion criteria, the included studies are not quite the same.…”
Section: Discussioncontrasting
confidence: 71%
“…Statistically, PENG block seemed to be as effective as other types of nerve blocks for alleviating pain after hip surgery. We note that the pooled result of postoperative 24-h morphine consumption in published relevant meta-analysis is inconsistent with ours (27). Due to different perspectives and inclusion criteria, the included studies are not quite the same.…”
Section: Discussioncontrasting
confidence: 71%
“…The articular branches of the FN, ON and AON are consistently found here. A pooled meta-analysis done by Huda et al demonstrated complete analgesia with less incidence of motor blockade and better range of motion leading to a shorter time to first walk postoperatively with PENG block in patients with hip arthroplasty [ 14 ]. The encouraging results were found with PENG block over other regional blocks as well such as femoral nerve block or fascia iliaca compartment block with no differences in static and dynamic pain scores as well as cumulative opioid consumption during 48 hours with preservation of quadriceps muscle strength after total hip arthroplasty [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…This will help to enhance the quality and duration of analgesia as observed by Jadon et al and Roy et al [ 16 , 17 ]. Many authors have used PENG block with different volumes of local anesthetics from 10 ml to 30 ml to provide analgesia after hip surgery, which could obscure the discrepancy of their results [ 14 - 20 ]. Reviewing the fluoroscopic and cadaveric study, the spread of 5, 10, 15 and 20 ml dye when injected below the psoas tendon and over the superior pubic ramus, adequate diffusion was found with 10 ml volume as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huda AU et al showed similar results regarding opioid consumption within the first 24 hours and duration of analgesia. They concluded that PENG block for hip surgery patients is associated with a substantial decrease in opioid intake (0.54 mg) in the first 24 hours following surgery (p=0.05) and increased duration of analgesia in the postoperative period [ 10 ]. Based on our study, the time for the first rescue analgesic requirement was substantially more in group B (445.0 minutes) than in group A (388.9 minutes) (p<0.05).…”
Section: Discussionmentioning
confidence: 99%